Social inclusion and social exclusion: A necessary conceptual discussion - Denkewicz, Patricia (Seven Editora, 2024)
Society, historically, experiences several social processes, including social inclusion and social exclusion. Complex concepts that help understand social, economic, political and cultural inequalities. It is understood that the interpretation of these concepts in a broader way is necessary to effectively develop inclusive actions and to alleviate exclusionary processes, seeking social justice. Therefore, this study aims to discuss the mechanisms, processes and consequences of social inclusion and social exclusion in contemporary social reality. Regarding methodology, a qualitative and descriptive approach was chosen, with data collection based on bibliographical research. It is concluded that debating the processes of social inclusion and social exclusion in contemporary society shows that in addition to the complexity intrinsic to social dynamics and the challenges faced by different groups and individuals, the aforementioned concepts are polysemic and their discussion occurs historically, since relationships social conditions permeate the existence of humanity. DOI:https://doi.org/10.56238/sevened2024.007-069